Ecomorphology of a predatory deep-sea fish family: does trophic specialization drive hyperspeciation? - McGonagle, Ryan P.; Kerstetter, David W.; Fenolio, Danté; Sutton, Tracey T. (Frontiers in Marine Science, 2023)
Two of the main drivers of speciation among aquatic vertebrates are physical isolation (e.g., lakes and streams) and micro-niche availability (e.g., tropical reefs). In both regards, the mesopelagic domain of the open ocean, Earth’s second largest cumulative ecosystem (behind only the bathypelagic domain), would seem retardant. Ocean circulation makes isolation rare on both contemporary and geological time/space scales, and the lack of substrate precludes stable micro-niches. Paradoxically, some pelagic taxa demonstrate much higher-than-expected species richness on regional scales. A prime example is the dragonfish family Stomiidae, the most speciose family of mesopelagic fishes, owing largely to the subfamily Melanostomiinae (scaleless black dragonfishes), which contributes 222 of the 320 described species. Within genera, species are differentiated almost solely by form of the jugular-positioned, bioluminescent barbel, a structure putatively linked to feeding (via prey luring). The relationship between diversity (both systematic and morphological) and diet within the Melanostomiinae has not been previously examined, primarily due to sample size limitation. Herein, the diet and morphology of 16 species of melanostomiine dragonfishes from the Gulf of Mexico were examined to ascertain whether the diversification in this fish clade is based on prey specialization, as is the case with many other speciose fish families (e.g., Cichlidae). Gut content analysis revealed a rather small spectrum of prey taxa across a wide spectrum of predators, with most species exhibiting piscivory centered on the most regionally abundant lanternfishes (Myctophidae). Lesser numbers of species preyed upon bristlemouths (Gonostomatidae), oceanic basslets (Howellidae), bigscales (Melamphaidae), and other dragonfishes, while three species selected for cephalopod prey. No dragonfish species consumed macrocrustaceans (e.g., decapod shrimps), despite their numerical prevalence as potential prey. Regarding functional morphology, dissimilarity was driven mostly by barbel length, vertical oral gape, and horizontal maxillary oral gape. There were no robust morphological-dietary relationships amongst melanostomiines, with dietary diversity much lower than morphological diversity. These results suggest that other factors, perhaps conspecific recognition and/or sexual selection related to spawning, may be primary drivers of hyperspeciation in the micro-habitat-poor pelagic environment.